Competition Policy and Property Rights. - Vickers, J (Macmillan Publishers, 2010)
One of the most controversial questions in current competition policy is when, if ever, should competition law require a firm with market power to share its property, notably intellectual property, with its rivals? And if supply is required, on what terms? These questions are discussed with reference to recent law cases including the EC Microsoft judgment of 2007 and the US linkLine case of 2009. The analysis focuses on whether competition law and regulation are complements or substitutes and on incentives for investment and (sequential) innovation.